Synergistic Effect of Melatonin and Selenium Improves Resistance to Postharvest Gray Mold Disease of Tomato Fruit - Zang, Huawei; Ma, Jiaojiao; Wu, Zhilin; Yuan, Linxi; Lin, Zhi-Qing; Zhu, Renbin; Bañuelos, Gary S.; Reiter, Russel J.; Li, Miao; Yin, Xuebin (Frontiers in Plant Science, 2022)
Melatonin (MT) is a ubiquitous hormone molecule that commonly distributes in nature. MT not only plays an important role in animals and humans but also has extensive functions in plants. Selenium (Se) is an essential micronutrient for animals and humans, and is a beneficial element in higher plants at low concentrations. Postharvest diseases caused by fungal pathogens lead to huge economic losses worldwide. In this study, tomato fruits were treated with an optimal sodium selenite (20 mg/L) and melatonin (10μmol/L) 2 h and were stored for 7 days at room temperature simulating shelf life was identified, and the synergistic effects of Se and MT collectively we called Se-Mel on gray mold decay in tomato fruits by Botrytis cinerea was investigated. MT did not have antifungal activity against B. cinerea in vitro, while Se significantly inhibited gray mold development caused by B. cinerea in tomato. However, the interaction of MT and Se showed significant inhibition of the spread and growth of the disease, showing the highest control effect of 74.05%. The combination of MT with Se treatment enhanced disease resistance of fruits by improving the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well increasing the gene expression level of pathogenesis-related (PR) proteins. Altogether, our results indicate that the combination of MT and Se would induce the activation of antioxidant enzymes and increase the expression of PR proteins genes that might directly enhance the resistance in tomato fruit against postharvest pathogenic fungus B. cinerea.